Penjadwalan Tenaga Kerja Pada Hotel Menara Lexus Menggunakan Algoritma Genetika - Rohima Almahuwanah; Sajaratud Dur; Hendra Cipta (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
Labor scheduling is allocating human resources to work stations according to needs. To increase productivity, companies must schedule labor optimally. In allocating labor, the Hotel Menara Lexus company has implemented labor scheduling with 3 work shifts, namely morning, afternoon and night. Because scheduling is still made manually, it is possible for schedule "collisions" to occur and there is no fairness in the distribution of shifts to each employee. To solve this problem, an appropriate algorithm is needed so that the scheduling process can run optimally. The application of genetic algorithm methods in scheduling problems is able to produce good solutions using chromosome representation, determining objective function values, fitness evaluation, determining probability function values, selection process using Roulette Wheel, crossover method using one cut-point crossover, and mutation at the above level. 0.5 can then be generated. From parameter testing, the results obtained